The Research of the Influence on Stress below the Roadway Floor of the Coal Seam Becoming Thin. (21st March 2022) - Chen, Liang; Liu, Qi
Abstract : Stress is the important factor of dynamic disaster in the coal mine. Stress is closely related with surrounding geological conditions. The geological tectonic area which exists high stress has a greater impact on dynamic disaster. However, local changes of the coal seam in the thickness may be sedimentary in origin and also result in the dynamic disasters. The paper studies the influence on stress with coal seam thickness varying below the roadway floor by means of numerical models. And the degree of influence on stress of the thinning with the burial depth is studied, too. The results of the research carried out were similar to the field test. Meantime, the results show that the shorter and narrower of the coal seam with thinning, the greater both horizontal and vertical stresses generated in that area. The difference is that the horizontal overstress increment is more than the vertical's. It also reveals an overstress phenomenon has a great relationship with the geometry of the coal seam more and not the burial depth of the heading face. The results drawn in this paper may be helpful to predict and control dynamic disasters when the geometry of the coal seam varies.